(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Olaru YU. YU. The concept of "creativity" in the system of training future economists in higher education. The article attempts to uncover the essence of the concept of «creativity» in the training of future economists in higher education. Proved the relationship of the creative component of the personal education of future professionals in economics education creative learning environment.